Rancang Bangun Website Company Profil Pusat Pelatihan Pertanian Pedesaan Swadaya Bheger Pemalang - wahyu sulistiyo; Aisyatul Karima; Afandi Nur Aziz Thohari; Eri Eli Lavindi; Fahriah, Sirli (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
Information is an important factor in the era of globalization. Service providers in the agricultural sector are not immune from the need for information. In the right way, information can be delivered on target. One way to introduce an agency or community is by processing information and building an information system. The information system can make it easier for the bureaucracy to introduce the Bheger Self-Help Rural Agricultural Training Center or commonly known as "P4S Bheger" to the community. One of the information systems that will be created to help P4S Bheger is a company profile website. Because to introduce an agency in this era, a company profile website is needed. The Bheger Self-Help Rural Agricultural Training Center or commonly known as "P4S Bheger" still uses manual methods in its management or introduction to the community. What has been done is using social media. This was felt to be inefficient, because a special place was needed to accommodate all information related to the Bheger Self-Help Rural Agricultural Training Center. The aim of this research is to build a company profile website. The results of the design of the company profile website which consists of home, about, contact and product menus help introduce P4S Bheger to the